Endothelial cell‐derived oxysterol ablation attenuates experimental autoimmune encephalomyelitis. (30th January 2023) - Ruiz, Florian; Peter, Benjamin; Rebeaud, Jessica; Vigne, Solenne; Bressoud, Valentine; Roumain, Martin; Wyss, Tania; Yersin, Yannick; Wagner, Ingrid; Kreutzfeldt, Mario; Pimentel Mendes, Marisa; Kowalski, Camille; et al.
Abstract: The vasculature is a key regulator of leukocyte trafficking into the central nervous system (CNS) during inflammatory diseases including multiple sclerosis (MS). However, the impact of endothelial‐derived factors on CNS immune responses remains unknown. Bioactive lipids, in particular oxysterols downstream of Cholesterol‐25‐hydroxylase (Ch25h), promote neuroinflammation but their functions in the CNS are not well‐understood. Using floxed‐reporter Ch25h knock‐in mice, we trace Ch25h expression to CNS endothelial cells (ECs) and myeloid cells and demonstrate that Ch25h ablation specifically from ECs attenuates experimental autoimmune encephalomyelitis (EAE). Mechanistically, inflamed Ch25h‐deficient CNS ECs display altered lipid metabolism favoring polymorphonuclear myeloid‐derived suppressor cell (PMN‐MDSC) expansion, which suppresses encephalitogenic T lymphocyte proliferation. Additionally, endothelial Ch25h‐deficiency combined with immature neutrophil mobilization into the blood circulation nearly completely protects mice from EAE. Our findings reveal a central role for CNS endothelial Ch25h in promoting neuroinflammation by inhibiting the expansion of immunosuppressive myeloid cell populations. Synopsis: Cholesterol 25‐hydroxylase (Ch25h) expression increases in central nervous system‐endothelial cells (ECs) during inflammation and regulates lipid secretion. Partial loss of Ch25h in ECs promotes polymorphonuclear myeloid‐derived suppressor cell (PMN‐MDSC) expansion and reduces experimental autoimmune encephalomyelitis (EAE) severity. Ch25h expression and related 25‐hydroxycholesterol (25‐OHC) are increased in ECs during neuroinflammation. Ch25h‐specific ablation from the microvascular endothelium alters fatty acid desaturase 2 (FADS2) expression, which promotes the production of anti‐inflammatory lipids, in particular Prostaglandin E2 (PGE2). 25‐OHC and PGE2 control PMN‐MDSC expansion. Partial loss of Ch25h promotes PMN‐MDSC accumulation within the central nervous system (CNS) and attenuates EAE. Abstract : Cholesterol 25‐hydroxylase (Ch25h) expression increases in central nervous system‐endothelial cells (ECs) during inflammation and regulates lipid secretion. Partial loss of Ch25h in ECs promotes polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSC) expansion and reduces experimental autoimmune encephalomyelitis (EAE) severity.